Central Pain Mimicking Trigeminal Neuralgia as a Result of Lateral Medullary Ischemic Stroke - Abinayaa Ravichandran; Kareem S. Elsayed; Hussam A. Yacoub (Case Reports in Neurological Medicine)
Background. Central pain mimicking trigeminal neuralgia (TN) as a result of lateral medullary infarction or Wallenberg syndrome has been rarely reported. Case Report. We discuss a patient who presented with a lateral medullary infarct and shortly after developed facial pain mimicking TN. We also elaborate on the anatomical pathway of the trigeminal nerve explaining facial pain as a result of a lateral medullary lesion. Discussion. Clinicians should be aware of this typical complication of lateral medullary infarct in order to attain proper management and work-up.